Adequate Number of Swallows for Pharyngeal Pressure Measurement of a Subject using High-resolution Manometry - Tsuyumu, Matsusato; Hama, Takanori; Kato, Takakuni; Kojima, Hiromi (International Archives of Otorhinolaryngology, 2020)
Introduction The number of pressure measurements that need to be recorded using high-resolution manometry (HRM) for the accurate evaluation of pharyngeal function is not well established.Objective The purpose of this study is to clarify the number of swallows required to obtain an accurate pharyngeal manometric profile of a person.Methods Forty healthy adults performed a dry swallow and bolus swallows using 3-, 5-, or 10 ml of water and underwent measurements using the Starlet HRM system. Each subject underwent 10 swallows for each of the four bolus volume conditions.Results The mean of up to seven measurements of maximum pre-swallow upper esophageal sphincter pressure with 10 ml of swallow was close to the mean of up to eight measurements in 95% of the subjects. Similarly, the rate of change of the average for the eighth and ninth measurements and the rate of change for the average of the ninth and tenth measurements were less than 5%. When the other parameters were similarly measured up to the sixth measurement, no major change in the average value was observed even if more measurements were taken.Conclusion A minimum of six measurements are required, and seven swallows are sufficient for evaluating the pharyngeal manometric profile of a single person. This number of measurements can be a useful criterion when performing HRM measurements on individual subjects.
Keywords: manometry methods; pharynx physiology; upper esophageal sphincter